2011
DOI: 10.1016/j.bbmt.2010.12.708
|View full text |Cite
|
Sign up to set email alerts
|

Influence of GST Gene Polymorphisms on the Clearance of Intravenous Busulfan in Adult Patients Undergoing Hematopoietic Cell Transplantation

Abstract: Intravenous (i.v.) busulfan can produce a more consistent pharmacokinetic profile than oral formulations can, but nonetheless, significant interpatient variability is evident. We investigated the influence of polymorphisms of 3 GST isozyme genes (GSTA1, GSTM1, and GSTT1) on i.v. busulfan clearance. Fifty-eight adult patients who received 3.2 mg/kg/day of busulfan as conditioning for hematopoietic cell transplantation were included in this study. Stepwise multiple linear regression demonstrated that GSTA1 varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
68
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 39 publications
4
68
3
Order By: Relevance
“…17,26,27,[30][31][32] The compensatory action of other GST isoforms to defective enzyme activity has been also demonstrated. 39 We did not find clear combined effect or interaction between GSTM1 and GSTA1 genotypes. However, it is worth noting that the distribution of the genotypes was not completely random.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…17,26,27,[30][31][32] The compensatory action of other GST isoforms to defective enzyme activity has been also demonstrated. 39 We did not find clear combined effect or interaction between GSTM1 and GSTA1 genotypes. However, it is worth noting that the distribution of the genotypes was not completely random.…”
Section: Discussioncontrasting
confidence: 58%
“…Another study conducted in adult patients found reduced i.v. BU CL in individuals with combined GSTM1 and GSTT1 null genotypes, but not in individuals with GSTM1 null genotype alone, 39 whereas others reported absence of such association. 17,26,27,[30][31][32] The compensatory action of other GST isoforms to defective enzyme activity has been also demonstrated.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The effect of polymorphisms in GSTA1 and GSTM1 on BU pharmacokinetics in adults has been studied before by Kusama et al, 21 Kim et al 22 and Abassi et al 19 The first two studies were carried out on Asian patients. In both studies no GSTA1*B homozygotes were observed.…”
Section: Discussionmentioning
confidence: 99%